Rapid detection of alkanes and polycyclic aromatic hydrocarbons - Coulon, Frederic; Mouazen, Abdul; Nawar, Said; Alamar, M. Carmen; Douglas, Reward K. (Cranfield University, 2018)
Vis-NIR data spectra analysis and chemometric modelling
Keywords: 'Near infrared spectroscopy'; 'chemometric techniques'; 'Environmental Monitoring'